The Ostomy Adjustment Scale: translation into Norwegian language with validation and reliability testing - Indrebø, Kirsten Lerum; Andersen, John Roger; Natvig, Gerd Karin (Journal of wound, ostomy, and continence nursing, 2014)
The purpose of this study was to adapt the Ostomy Adjustment Scale to a Norwegian version and to assess its construct validity and 2 components of its reliability (internal consistency and test-retest reliability). One hundred fifty-eight of 217 patients (73%) with a colostomy, ileostomy, or urostomy participated in the study. Slightly more than half (56%) were men. Their mean age was 64 years (range, 26-91 years). All respondents had undergone ostomy surgery at least 3 months before participation in the study. The Ostomy Adjustment Scale was translated into Norwegian according to standard procedures for forward and backward translation. The questionnaire was sent to the participants via regular post. The Cronbach alpha and test-retest were computed to assess reliability. Construct validity was evaluated via correlations between each item and score sums; correlations were used to analyze relationships between the Ostomy Adjustment Scale and the 36-item Short Form Health Survey, the Quality of Life Scale, the Hospital Anxiety & Depression Scale, and the General Self-Efficacy Scale. The Cronbach alpha was 0.93, and test-retest reliability r was 0.69. The average correlation quotient item to sum score was 0.49 (range, 0.31-0.73). Results showed moderate negative correlations between the Ostomy Adjustment Scale and the Hospital Anxiety and Depression Scale (-0.37 and -0.40), and moderate positive correlations between the Ostomy Adjustment Scale and the 36-item Short Form Health Survey, the Quality of Life Scale, and the General Self-Efficacy Scale (0.30-0.45) with the exception of the pain domain in the Short Form 36 (0.28). Regression analysis showed linear associations between the Ostomy Adjustment Scale and sociodemographic and clinical variables with the exception of education. The Norwegian language version of the Ostomy Adjustment Scale was found to possess construct validity, along with internal consistency and test-retest reliability. The instrument is sensitive for sociodemographic and clinical variables pertinent to persons with urostomies, colostomies, and ileostomies.